Flying lightness : promises for structural elegance. - Beukers, Adriaan, ....-; van Hinte, Ed, 1951- (Rotterdam : 010, 2005)
Flying Lightness paints a heroic picture of a century of aircraft development against the background of steadily increasing travel speeds. Yet since the Wright brothers made their first brief flight over 100 years ago, aircraft construction seems to have become strangely stuck in a rut. Today, rapid advances in the field of composites are opening up new possibilities for optimizing aircraft configurations and revising structural principles. Composites are combinations of two or more physically distinct materials that enhance each other's properties. The new modes of system integration and improved structural quality they offer may even manage to produce a 30 per cent more efficient 'blended wing' passenger plane. Flying wings, once just a footnote in the history of air transport, could well become the aircraft of the 21st century.